Additives to elephant grass ensilage. II. Silage quality and sampling - de Andrade, João Batista (1998)
Silages of Pennisetum purpureum Schum. cv. Guaçu prepared with 0, 8, 16 and 24% of ground ear corn with husks, wheat bran and saccharin, dry weight of additive/wet weight of green chop basis. The experimental design was a randomized blocks one in split-plot; the plots were the additives and levels, and the sub-plots the sampling methods. The material was ensiled using plastic vessels in middle of which holed pvc pipes (3 inches diameter) were put. These pipes (one per vessel) had the same length as the height of the vessels, and were filled at the same time and compacted the same way as the vessels. The first method of sampling used the material ensiled inside the pvc pipe, which was lifted out from the vessel at the moment of the silo opening. The other sampling method, normaly used in digestibility trials, consisted of samples composed by daily sub-samples collected in the vessels. The pvc sampling method was more efficient because it sampled a profile of the whole silage. All of the silages showed high percentages of lactic acid and low percentages or even absence of butyric acid, though in all silages high ammoniacal-N percentages were detected.